1999
DOI: 10.15394/jaaer.1999.1219
|View full text |Cite
|
Sign up to set email alerts
|

Crew Resource Management: A Literature Review

Abstract: Crew Resource Management as an academic field of study has only been in existeice for a relatively short period.However, because of its importance to the aviation community and the airlines in particular, there is a small but growing community of researcher and academicians that are specializing in its postulates. Despite the importance of research to the aviation industry and to aviation education, no comprehensive compendium of point specific literature exists. This void presents an obstacle for both researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…HROs such as aviation, military and automotive industries also developed crew resource management (CRM) training programmes, which were complementary to the simulation-based team training with debriefing sessions, but put more emphasis on non-technical skills [ 53 ]. These included effective leadership, teamwork, dealing with diverse personalities and operating styles, workload management and situational awareness; preparation, planning, and vigilance; workload distribution, distraction avoidance; individual factors, and stress reduction [ 53 ]. A US study showed significant improvement in safety, efficiency, dependability and assertiveness amongst aviation managers following CRM training [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HROs such as aviation, military and automotive industries also developed crew resource management (CRM) training programmes, which were complementary to the simulation-based team training with debriefing sessions, but put more emphasis on non-technical skills [ 53 ]. These included effective leadership, teamwork, dealing with diverse personalities and operating styles, workload management and situational awareness; preparation, planning, and vigilance; workload distribution, distraction avoidance; individual factors, and stress reduction [ 53 ]. A US study showed significant improvement in safety, efficiency, dependability and assertiveness amongst aviation managers following CRM training [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using CRM to help deconstruct and learn from safety incidents in healthcare could lead to a greater understanding of the importance of non-technical skills and improvements in safety [ 69 , 71 , 73 ]. CRM was adapted to healthcare, resulting in care improvement and harm reduction across a wide variety of medical specialties [ 53 , 74–76 ]. When implemented in the operating rooms, CRM has been shown not only to improve communication and staff morale but also to reduce patient morbidity and mortality [ 53 , 74 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu programla birlikte hava yolu işletmelerinin ihtiyaçlarına uygun daha yenilikçi eğitimleri takip edebilmeleri mümkün hale gelmiştir. Bu eğitim olanaklarıyla birlikte hava yolları işletmeleri tüm uçuş ekiplerine hat uçuş eğitimleri ile birlikte ekip kaynak yönetimi eğitimlerini birlikte verme, uçuş ekiplerinin teknik eğitimleriyle ekip kaynak yönetimi eğitimlerini bütünleştirme fırsatını bulmuşlardır (Kaps, Keren-Zvi ve Ruiz, 1999) Beşinci nesil EKY ise, tehdit ve hata yönetimi kavramını ortaya koyar. Burada, EKY hata yönetimi ve azaltılması stratejisi olarak yerini alır.…”
Section: Ekip Kaynak Yönetimi: Gelişim Süreciunclassified